2022
DOI: 10.1155/2022/2255533
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits as Predictors of Self-Regulated Learning and Academic Engagement among College Students in Ghana: A Dimensional Multivariate Approach

Abstract: The study explored personality traits as they predicted self-regulated learning and academic engagement among college students in Ghana. A sample of 652 (return rate was 87.0%) was drawn from an accessible population of 17,396. Adapted versions of Taiwanese Short Self-Regulation Questionnaire (22 items; α = 0.84), University Student Engagement Inventory (15 items; α = 0.81), and Big-Five Personality Inventory (30 items; α = 0.70) were used for the data collection. The data collected were analysed using multiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Regarding the relationship between personality traits and selfregulated learning, the results are various. Some studies have identified a positive relationship between conscientiousness, openness, agreeableness, extraversion and neuroticism and self-regulated learning strategies (Mahama et al, 2022;Rosito, 2020;Kirwan, Lounsbury & Gibson, 2014;Babakhani, 2014;Eilam, Zeidner & Aharon, 2009), while other authors consider that there is no correlation between personality traits and self-regulated learning strategies, but rather they overlap (Bidjeramo & Dai, 2007;McCrae & Costa, 1987), arguing that personality traits include self-regulation tendencies. A limitation of this paper could be the non-identification of all the studies performed on this topic, which could prevent the generalization of the results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding the relationship between personality traits and selfregulated learning, the results are various. Some studies have identified a positive relationship between conscientiousness, openness, agreeableness, extraversion and neuroticism and self-regulated learning strategies (Mahama et al, 2022;Rosito, 2020;Kirwan, Lounsbury & Gibson, 2014;Babakhani, 2014;Eilam, Zeidner & Aharon, 2009), while other authors consider that there is no correlation between personality traits and self-regulated learning strategies, but rather they overlap (Bidjeramo & Dai, 2007;McCrae & Costa, 1987), arguing that personality traits include self-regulation tendencies. A limitation of this paper could be the non-identification of all the studies performed on this topic, which could prevent the generalization of the results.…”
Section: Discussionmentioning
confidence: 99%
“…This is probably why conscientiousness is considered the most important variable of all five belonging to personality, when it comes to school achievements (Roberts et al, 2005). At the same time, as regards the relationship between conscientiousness and self-regulated learning, it has been proven that conscientiousness is positively associated with selfregulated learning strategies, which ultimately lead to good academic results (Mahama et al, 2022;Rosito, 2020;Bruso, Stefaniak & Bol, 2020;Kirwan, Lounsbury & Gibson, 2014;Babakhani, 2014;Eilam, Zeidner & Aharon, 2009). A possible explanation for the relationship between self-regulated learning and conscientiousness may be that students who have self-regulatory skills tend to be consistent and responsible in order to attend classes, to meet deadlines and the requirements of their class (Kirwan, Lounsbury & Gibson (2014).…”
Section: The Relationship Between Personality Self-regulated Learning...mentioning
confidence: 99%
See 2 more Smart Citations